Genetic Characterization of Highly Pathogenic Avian Influenza A(H5N1) Clade 2.3.4.4b, Antarctica, 2024 - Victor Neira; Naomi Ariyama; Pablo N. Castillo-Torres; Barbara Brito; Gabriela Muñoz; Karla B. Díaz Morales; Leonardo I. Almonacid; Benjamín Bennett-Laso; Barbara Berazay; Miloš Barták; Rafael Medina; Marcelo González-Aravena; et al. (Emerging Infectious Diseases, 2025)
In 2024, we sequenced highly pathogenic avian influenza virus A(H5N1) clade 2.3.4.4b genomes isolated from 5 brown skuas from James Ross Island, Antarctica. Phylogenetic analysis suggested the virus reached Antarctica through South America. Continued genetic surveillance will be critical to elucidate H5N1 virus transmission dynamics within Antarctica and surrounding areas.